2011
DOI: 10.1093/europace/eur171
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine predicts appropriate implantable cardioverter-defibrillator intervention in patients with left ventricular dysfunction

Abstract: Asymmetric dimethylarginine and the Arg/ADMA ratio seem to be new biomarkers for the prediction of ventricular tachycardia/ventricular fibrillation episodes and of appropriate ICD intervention in pts with left ventricular ejection fraction dysfunction (LV-EF ≤ 35%), suggesting a value for risk stratification in these pts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…10 In a study of 106 primary prevention ICD patients from Germany, ADMA was also found to be associated with the risk of appropriate ICD therapy. 11 Unlike ADMA, its structural isomer SDMA, has been less well investigated and is thought to be biologically inert as it does not directly inhibit NO synthesis. 12 However, recent studies have reported associations of SDMA with cardiovascular outcomes and mortality in various study populations including patients undergoing coronary angiography, 10 and with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a study of 106 primary prevention ICD patients from Germany, ADMA was also found to be associated with the risk of appropriate ICD therapy. 11 Unlike ADMA, its structural isomer SDMA, has been less well investigated and is thought to be biologically inert as it does not directly inhibit NO synthesis. 12 However, recent studies have reported associations of SDMA with cardiovascular outcomes and mortality in various study populations including patients undergoing coronary angiography, 10 and with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%